Child Mortality Transition in the Arabian Gulf: Wealth, Health System Reforms, and Development Goals - Salam, Asharaf Abdul; Al-Khraif, Rshood M. (Frontiers in Public Health, 2020)
Background: Child mortality is the most crucial indicator of national progress and a reflection of not only the health system performance but also the wealth (budget) utilization and goal achievements. Many developing nations have recorded progress in this dimension but those of the Arabian Gulf (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and United Arab Emirates) show remarkable progress and achievements. Methods: Using the latest update of United Nations Inter-agency Group for Child Mortality Estimation 2017, an attempt is made here to review and appraise their achievements in child mortality reduction since 1950s taking into account Under 5 mortality, infant mortality, and neonatal mortality. Results: This review finds a rapid decline in child mortality in the Arabian Gulf in a short span of 50 years, which is in line with the achievement of Sustainable Development Goals. Conclusions: There is a remarkable budget allocation and investment in health system building, improving the other contributing sectors like water, sanitation, hygiene, nutrition, and life style modifications apart from the usual health care interventions.